2015
DOI: 10.1016/j.bpj.2015.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Slowdown of Interhelical Motions Induces a Glass Transition in RNA

Abstract: RNA function depends crucially on the details of its dynamics. The simplest RNA dynamical unit is a two-way interhelical junction. Here, for such a unit--the transactivation response RNA element--we present evidence from molecular dynamics simulations, supported by nuclear magnetic resonance relaxation experiments, for a dynamical transition near 230 K. This glass transition arises from the freezing out of collective interhelical motional modes. The motions, resolved with site-specificity, are dynamically hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…However, we have calculated the local translational and reorientational dynamics of SAM-I RNA and water molecules: (i) for translational dynamics, we estimated the positional autocorrelation (Figure S20) between local structural trapped water molecule of SAM-I as indexed A as indicated in Figure b and its interacting RNA atoms, (ii) and in the case of reorientational relaxation, we compare the single-bonded N–H and P–O dipole vector’s (N–H and P–O bonds of the peripheral residues 59–65, 86–88 of SAM-I core) reorientational relaxation with the core–shell (0–5 Å) water molecules relaxation kinetics (see Table , Figure S21a,b and Table S8 in the Supporting Information), which evidently show that the slowest time component (τ 1 ) of water relaxation and structural reorientational relaxation of RNA (N–H and P–O bond vectors) are dynamically coupled (∼ns). The time scale is comparable with that observed in the NMR experiment …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, we have calculated the local translational and reorientational dynamics of SAM-I RNA and water molecules: (i) for translational dynamics, we estimated the positional autocorrelation (Figure S20) between local structural trapped water molecule of SAM-I as indexed A as indicated in Figure b and its interacting RNA atoms, (ii) and in the case of reorientational relaxation, we compare the single-bonded N–H and P–O dipole vector’s (N–H and P–O bonds of the peripheral residues 59–65, 86–88 of SAM-I core) reorientational relaxation with the core–shell (0–5 Å) water molecules relaxation kinetics (see Table , Figure S21a,b and Table S8 in the Supporting Information), which evidently show that the slowest time component (τ 1 ) of water relaxation and structural reorientational relaxation of RNA (N–H and P–O bond vectors) are dynamically coupled (∼ns). The time scale is comparable with that observed in the NMR experiment …”
Section: Discussionsupporting
confidence: 81%
“…However, we have calculated the local translational and reorientational dynamics of SAM-I RNA and water molecules: (i) for translational dynamics, we estimated the positional autocorrelation (Figure S20) between local structural trapped water molecule of SAM-I as indexed A as indicated in Figure b and its interacting RNA atoms, (ii) and in the case of reorientational relaxation, we compare the single-bonded N–H and P–O dipole vector’s (N–H and P–O bonds of the peripheral residues 59–65, 86–88 of SAM-I core) reorientational relaxation with the core–shell (0–5 Å) water molecules relaxation kinetics (see Table , Figure S21a,b and Table S8 in the Supporting Information), which evidently show that the slowest time component (τ 1 ) of water relaxation and structural reorientational relaxation of RNA (N–H and P–O bond vectors) are dynamically coupled (∼ns). The time scale is comparable with that observed in the NMR experiment We have also investigated the correlation between the functional dynamics of kink-turn (KT) and core regions with the hydration dynamics in connection with the experimental results as summarized below: (a) Role of site-specific water controlling kink-turn dynamics: Early experiments proposed an ion environment-dependent conformational fluctuation of this KT motif in solution in the case of SAM-I riboswitch RNA. , With a variety of structure-probing experiments, the above two experimental results suggested that the bimodal stability of the kink-turn motif is important for the riboswitch function.…”
Section: Discussionmentioning
confidence: 77%
“…Hydration affects the dynamics of RNA significantly more than those of a globular protein (lysozyme). In fact, as reported, the structural differences between RNA and protein result in slower dynamics, motional heterogeneity, and heterogeneous hydration on the molecular surface of RNA . Yet, the DT of RNA (like protein) is initiated by sudden change of hydration water mobility at its FSC temperature .…”
Section: Introductionmentioning
confidence: 73%
“…Subsequently while heating, bimolecular motions as often measured by atomistic mean-square displacement (MSD) increase linearly with temperature up to certain onset temperature, at which suddenly they exhibit a sharp transition to a nonlinear temperature dependence. In parallel with the glass transition temperature in a glassy substance, the onset temperature of anharmonicity in a biomolecular system is referred to as the dynamical transition (DT) temperature, T DT .…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of the simulated MD trajectories presented by Frank et al (10) includes extraction of global motions through principal component analysis, as well as specifics of the motions of individual bond vectors. The analysis shows that even in this system, designed to be simple to interpret, there is motional heterogeneity along the molecule in addition to the approximately threedimensional hinge-bending motion of the two helical segments.…”
mentioning
confidence: 99%